Orthodoxy in the Context of Modern Russian-Chinese Relations: the Views of Chinese Scholars - Zhe Liang (Vestnik RUDN. International Relations, 2015)
Orthodoxy is a significant symbol of the spiritual and social culture of Russia, is one of the factors of internal and foreign policy. Following the election of Vladimir Putin in 2012 as president, the Russian-Chinese relations have acquired a more intense character, and Orthodoxy has come to play an important role in them. Activities of Orthodox missionaries had largely influence on the development of not only the Russian-Chinese relations, but also on Sinology in Russia, which significantly strengthened the political and spiritual ties between the two countries. The article describes the history of the “orthodox issue” between Russia and China, reveals the views of Chinese scholars on the subject of Orthodoxy in the framework of strategic cooperation between the two countries at the present stage. Particular attention is given to the prospects of Orthodoxy in China and possible options for its promotion in this country. The study concludes that in the short term Orthodoxy won’t be widely popular in China due to various features, including government policy, special attitude to religion among the Chinese themselves, as well as unadjusted Orthodoxy for the PRC. However, according to the author, there is a chance that the situation will change with time.